Efektivitas Penerapan Strategi Everyone is a Teacher Here Untuk Meningkatkan Prestasi Siswa Kelas VIII.A SMPN 1 Gunungsari Pada Mata Pelajaran IPA - Lalu Ukir Ukir (Universitas Pendidikan Mandalika Mataram, 2019)
This research was conducted at Gunungsari 1 Public Middle School with the aimof knowing the effectiveness of the use of Everyone is A Teacher Here strategy inlearning activities, so that how far the results of student learning achievementimproved by using the learning strategy. This type of research is classroomaction research (CAR) ), which is carried out by the cycle of persiklus withseveral stages, namely: planning, implementation, observation and reflection.The data in this study are student learning activities and student learningoutcomes. The results of the study showed that the application of BeajarEveryone is a Teacher Here strategy was effective to improve students' learningachievement in grade VIII.A from cycle I to cycle II with an average score of 70 ,48 in the first cycle to 77.27, and classical completeness from the first cycle tothe second cycle experienced a significant increase of 59.38 to 87.5 while theresults of the analysis of the N-Gain test were 0.32 with the moderate category.Conclusions from the results of the study this is the application of the learningstrategy Everyone is a Teacher Here effectively increases the learning activitiesof Gunungsari 1 Junior High School students in class VIII.A so that learning ismore focused, absorbs more subject matter and is more fun for students. So itcan be concluded that the application of Everyone's a Teacher Here learningstrategy can effectively improve science learning achievement of students ofGunungsari 1 Junior High School class VIII.A from cycle I to cycle II.